2003
DOI: 10.1002/chem.200304573
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Bis(amino alcohol)oxalamide Gelators—Gelation Properties and Supramolecular Organization: Racemate versus Pure Enantiomer Gelation

Abstract: Four new chiral bis(amino alcohol)oxalamides (1-4: amino alcohol=leucinol, valinol, phenylglycinol, and phenylalaninol, respectively) have been prepared as low-molecular-weight organic gelators. Their gelation properties towards various organic solvents and mixtures were determined and these were then compared to related bis(amino acid) oxalamide gelators. Spectroscopic (FTIR, (1)H NMR) and X-ray diffraction studies revealed that the primary organization motif of (S,S)-1 and racemate 1 (rac-1) in lipophilic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 49 publications
6
83
0
Order By: Relevance
“…[28] This has led us to propose that a pair of enantiomers in contrast to a single enantiomer results in favorable p-p interactions and van der Waals interactions leading to the self-assembly of the supramolecular network of the organogel.…”
Section: Entries 2-5) a Halogen-substituted Chalcone (E)-3-(4-bromopmentioning
confidence: 99%
“…[28] This has led us to propose that a pair of enantiomers in contrast to a single enantiomer results in favorable p-p interactions and van der Waals interactions leading to the self-assembly of the supramolecular network of the organogel.…”
Section: Entries 2-5) a Halogen-substituted Chalcone (E)-3-(4-bromopmentioning
confidence: 99%
“…[11] and UNEGOJ (right). [12] Figure 5. Pie chart of frequency of space groups observed within Dr Kojić-Prodić's CSD entries.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Some of Biserka's most high-profile structures in the CSD include those of supramolecular organic gelators based on amino acid and amino alcohol oxalamides (Figure 4) -the publications associated with these structures have each been cited over 100 times. [11,12] Other key studies include the structural analysis of interaction behaviour in calixarene amino acid derivatives [13] and the structures of palladium(II) quinolinylaminophosphonate complexes. [14] Roughly two thirds of Biserka's CSD structures are organic, the remaining third containing at least one metal atom with an increasing fraction of polymeric coordination compounds since 2009.…”
Section: Biserka and The Csdmentioning
confidence: 99%
“…[12] In some cases, as has often been observed with many other gelator systems, very slight changes to the gelator structure can influence the gelation behaviour dramatically. [13] Chirality, for example, often determines whether a compound will function as a gelator or not. Whereas racemic mixtures are sometimes less efficient gelators than the corresponding enantiomerically pure products, [14,15] the opposite effect has been observed in other cases.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas racemic mixtures are sometimes less efficient gelators than the corresponding enantiomerically pure products, [14,15] the opposite effect has been observed in other cases. [13,16,17] Very recently, Hirst et al have shown that changing the chirality of one amino acid of a dendritic organogelator can lead to changes in the gelation behavior in organic solvents. [18] Herein we report that changes in chirality effect the gelation behaviour of amino acid-substituted 1,3,5-cyclohexyltricarboxamide derivatives in water (Scheme 1), which lead to novel hierarchical self-assembled systems.…”
Section: Introductionmentioning
confidence: 99%